(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
Naproxen (NPX), a nonsteroidal anti-inflammatory drug, commonly used for relief of a wide variety of pain, fever, inflammations, and stiffness, can end up in aquatic systems, due to inappropriate water treatment or disposal, and therefore represent nowadays a risk for the environment. This study investigated the NPX degradation upon ultrasonic action (630 kHz) under different experimental conditions. The effect of NPX concentration (3-65 μmol L-1) and ultrasonic power (20–60 W) were evaluated. Best performances were obtained at higher NPX concentrations and powers. In these conditions, NPX (65 μmol L-1) can be readily eliminated ( 120 min) by °OH coming from water and oxygen disociation. NPX sonochemical elimination followed a Langmuir-type kinetic model. However, even after long ultrasound irradiation times (4 h), more than 80% of total organic carbon (TOC) remained in the solution. Presence of Fe2+ increased both the removal and mineralization of NPX. The positive effect of iron ions was attributed to the generation of additional °OH coming from the reaction between these ions and the sono-generated hydrogen peroxide. The ultrasonic system combined with iron ions showed to be a promising alternative to the complete degradation of pharmaceutical products in waters.